(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Monetary policy plays a critical role in shaping economic outcomes, influencing inflation, employment,and economic growth. This paper provides a comprehensive review of monetary policy, focusing on its historical evolution, tools and instruments, impact on changing economic landscapes, critiques, challenges, and future directions. The historical evolution section traces the development of monetary policy from pre-20th century barter systems to modern digital currencies. The tools and instruments section examines key tools such as interest rates,open market operations, and forward guidance. The impact section discusses how globalization, technological advancements, demographic shifts, and financial innovation affect monetary policy. Critiques and challenges highlight issues such as the effectiveness of monetary policy, central bank independence, the zero lower bound, and political challenges. Future directions consider potential changes in policy frameworks, the role of central banks in addressing economic challenges, and the importance of international cooperation. Case studies analyze monetary policy responses to the 2008 financial crisis, the Eurozone crisis, and the COVID-19 pandemic. The paper concludes by emphasizing the need for flexible, innovative, and internationally coordinated monetary policy frameworks to address evolving economic challenges.